Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3892/ol.2020.11652
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA LINC00460 predicts poor survival and promotes cell viability in pancreatic cancer

Abstract: Emerging evidence has demonstrated that long non-coding RNAs (lncRNAs) possess great potential as vital biomarkers and powerful therapeutic targets in various diseases. In the present study, differentially expressed transcripts in pancreatic cancer (PC) were identified, and a competing endogenous RNA (ceRNA) network was constructed using The Cancer Genome Atlas database. An independent cohort consisting of 59 patients with PC was used to validate the clinical value of the identified lncRNA. Cell viability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that LINC00460 is a marker for poor OS prognosis across different tumors, such as CESC ( 48 ), HNSC ( 80 ), KIRC ( 81 ), LUAD ( 49 ) and PAAD ( 82 ). In addition, we describe here that LINC00460 high expression is significantly associated with poor survival in three different tumors (GBM, LGG and SARC) but related with a favorable survival rate in BRCA, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this finding, a recent study based on database and clinical sample analysis identified LINC00460 as a key lncRNA with prognostic value in pancreatic cancer. 36 These results suggest that LINC00460 might be regarded as a candidate for detection and therapy of PDAC. However, there is no research fully investigating the biological roles or mechanism of LINC00460 in PDAC.…”
Section: Discussionmentioning
confidence: 87%
“…Previous study suggested that LINC00460 level exhibits high expression in human prostate cancer tissues and cell lines, and downregulation of LINC00460 suppresses cell proliferation and promotes cell apoptosis in prostate cancer, which is consistent with our study [ 12 ]. Moreover, the LINC00460 level is positively related to tumor size, and predicts poor survival of PC patients [ 13 ]. Interestingly, our findings indicated that LINC00460 level was increased in pancreatic cancer cell lines (SW1990, HPAC, PaCa-2, CFPAC-1, CAPAN-1) compared to normal human pancreatic duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, LINC00460 downregulation could depress PC cell proliferation and promote cell apoptosis, mediated by PI3K/AKT pathway [ 12 ]. Moreover, LINC00460 may be a promising biomarker for diagnosis and prognosis of PC, and predicts poor survival of PC patients [ 13 ]. However, the underlying mechanism involved in LINC00460 playing its role in the proliferation, migration and invasion of pancreatic cancer cells has been uninvestigated.…”
Section: Introductionmentioning
confidence: 99%